PENGARUH BURSA SAHAM ASIA TERHADAP BURSA SAHAM INDONESIA - Ardi Kurnia Cahyadi; Harti Budi Yanti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2012)
This study examined the effect of the movement of Asian stock markets of Indonesia stock exchange. The data used is the composite stock price index data from the Japanese stock market, Hong Kong, Singapore and Indonesia. The data used are monthly data covering the period July 1997 to June 2008. To find out if there is a relationship of each stock on the stock exchange Indonesia Pearson correlation coefficient is used. Furthermore, to know the influence of other movements ofthestock exchanges Indonesia Granger Causality test is used. This research provides empirical evidence on the theory of contagion effect, by showing the influence of Asian stock markets of Indonesia stock market and vice versa. Testing the Granger test succeeded in proving the existence of a causal relationship between stock market Indonesia with Singapore stock exchange.